2011
DOI: 10.1620/tjem.225.203
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties Facing Physician Mothers in Japan

Abstract: Despite recent increases in the number of female physicians graduating in Japan, their premature resignations after childbirth are contributing to the acute shortage of physicians. Previous Japanese studies have explored supportive measures in the workplace, but have rarely focused on the specific problems or concerns of physician-mothers. Therefore, this study explored the challenges facing Japanese physician-mothers in efforts to identify solutions for their retention. Open-ended questionnaires were mailed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…In a survey of 249 female Japanese physicians, gender discrimination regarding career choice, discrimination and sexual harassment in the workplace, high levels of stress concerning family responsibility, and lack of support regarding pregnancy and childcare in the workplace were reported. 23 Female obstetrician-gynecologists surveyed were more likely than their male counterparts to be single and childless, and 34% reported receiving advice from colleagues and superiors to postpone childbirth. 21 Only 50% of male and female obstetrician-gynecologists surveyed could obtain maternity or paternity leave.…”
Section: Case 1: Japanmentioning
confidence: 98%
See 4 more Smart Citations
“…In a survey of 249 female Japanese physicians, gender discrimination regarding career choice, discrimination and sexual harassment in the workplace, high levels of stress concerning family responsibility, and lack of support regarding pregnancy and childcare in the workplace were reported. 23 Female obstetrician-gynecologists surveyed were more likely than their male counterparts to be single and childless, and 34% reported receiving advice from colleagues and superiors to postpone childbirth. 21 Only 50% of male and female obstetrician-gynecologists surveyed could obtain maternity or paternity leave.…”
Section: Case 1: Japanmentioning
confidence: 98%
“…21 Furthermore, childcare options in Japan are limited and expensive compared with other countries. 23 In 2009, the Japanese Medical Association reported that only 50% of hospitals had childcare centers onsite. 23 Unsurprisingly, given this environment, pregnancy and childcare appear to affect the number of hours worked and procedures performed by female physicians in Japan.…”
Section: Case 1: Japanmentioning
confidence: 99%
See 3 more Smart Citations